2017
DOI: 10.3177/jnsv.63.133
|View full text |Cite
|
Sign up to set email alerts
|

Medium-Chain Triglycerides in Combination with Leucine and Vitamin D Benefit Cognition in Frail Elderly Adults: A Randomized Controlled Trial

Abstract: SummaryThe combined supplementation of medium-chain triglycerides (MCTs), l-leucine-rich amino acids, and cholecalciferol (vitamin D3) increase muscle strength and function in frail elderly individuals. However, their effects on cognition are unknown. We enrolled 38 elderly nursing home residents (mean age6SD, 86.664.8 y) in a 3-mo randomized, controlled, parallel group trial. The participants were randomly allocated to 3 groups: the first group received a l-leucine (1.2 g)-and cholecalciferol (20 mg)-enriched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 26 publications
0
51
0
Order By: Relevance
“…However, the instruments used to assess cognitive outcomes were inconsistent among studies. Five studies used the Mini-Mental Status Examination [28,31,32,34,38], and four of them utilized the Alzheimer Disease Assessment Scale (ADAS-cog) [31,35,37,38]. Two studies used a neuroimaging (PET) endpoint: regional cerebral blood flow [30] or [11C]-acetoacetate tracer [28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the instruments used to assess cognitive outcomes were inconsistent among studies. Five studies used the Mini-Mental Status Examination [28,31,32,34,38], and four of them utilized the Alzheimer Disease Assessment Scale (ADAS-cog) [31,35,37,38]. Two studies used a neuroimaging (PET) endpoint: regional cerebral blood flow [30] or [11C]-acetoacetate tracer [28].…”
Section: Discussionmentioning
confidence: 99%
“…Three other studies did not show any significant weight change with KS [28,31,35]. Interestingly, Abe et al observed that participants improved their muscle mass and function [32]. Of note, those subjects received vitamin D and leucine in addition to the nutritional intervention, which may have contributed to this anabolic effect.…”
Section: Metabolic Effects Of Kd/ks In Cognitively Impaired Patients mentioning
confidence: 97%
See 2 more Smart Citations
“…After sniffing peppermint essential oil, the above amino acid metabolites were up-regulated and close to the normal level. Among them, leucine has been reported to improve the cognitive function of the frail elderly when combined with vitamin D [ 23 ].…”
Section: Discussionmentioning
confidence: 99%